Health risk behaviour and persistent and incident depression among middle-aged and older adults in South Africa. (March 2023) - Pengpid, Supa; Peltzer, Karl
The aim of this study was to assess the association between five health risk behaviours and persistent and incident depressive symptoms in a longitudinal study in South Africa. The sample included 5059 men and women (⩾40 years) in 2014/2015, and 4176 in 2018/2019 of the 'Health and Ageing in Africa: A Longitudinal Study of an INDEPTH Community in South Africa'. Depressive symptoms were assessed with the Centre for Epidemiologic Studies Depression scale. Multivariable logistic regression analysis was conducted to assess the associations between five health risk behaviours and persistent and incident depressive symptoms. Results indicate that 5.0% of participants had depressive symptoms at both wave 1 and 2 (persistent depressive symptoms), and 27.9% had incident depressive symptoms in wave 2. Higher education and moderate baseline physical activity were negatively associated and those with cardiovascular disease were positively associated with persistent depressive symptoms. Middle wealth index was negative, and being HIV positive and baseline tobacco use were positively associated with incident depressive symptoms. In conclusion, of five health risk behaviours assessed (inadequate fruit/vegetable intake, alcohol dependence, tobacco use, physical activity, and sedentary behaviour), only moderate physical activity was protective against persistent depressive symptoms, and tobacco use was associated with incident depressive symptoms.